CHICKEN INFECTIOUS ANEMIA VIRUS ANTIBODIES IN BREEDER BROILERS AND LEVELS OF PASSIVE TRANSFERENCE TO THE PROGENY - Quezada A., Benjamín (2008)
Three poultry farms (A, B and C) of Cobb breeder broilers were blood monitored at 30, 45, and 60 weeks of age to assess the level and persistence of sera antibodies against chicken infectious anemia virus (CIAV) under two vaccination strategies. Hens in farm A were vaccinated via drinking water and hens in farm B via intramuscular (IM) during the rearing period, whereas farm C was only exposed to a field virus. Progeny´s sera was evaluated at one day old to determine antibodies level and percent of transference. Serum samples were analyzed by a commercial ELISA test. A total seroconversion was detected in farms A and B at the age of 30 weeks while 10.5% of layers in farm C were negative. All hens in the three farms seroconverterd at 45 and 60 weeks old, but antibody titers decreased at the age of 60 weeks. The passive transference of antibodies to the progeny was much lower in farm A as compared to the other two farms.